1990
DOI: 10.21273/jashs.115.6.1019
|View full text |Cite
|
Sign up to set email alerts
|

Ovule Culture to Obtain Progeny from Hybrid Seedless Bunch Grapes

Abstract: Ovules of seedless bunch grapes (Vitis spp.) fertilized by controlled pollination increased in size during berry development. More ovules cultured 10 days or 60 to 70 days after pollination became brown compared to those cultured at 20 to 40 days. Cultured ovules developed with and without endosperm. Globular to torpedo stage embryos were recovered. More embryos and plants were recovered from ovules cultured at 40 or 60 days than at 10 or 20 days after pollination. Pollen par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
1
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 16 publications
2
39
1
1
Order By: Relevance
“…indole butyric acid (IBA), Ergostim, tartaric acid, L-glutamine and Lcysteine Emershad and Ramming (1984) Several genotypes Amino acids Emershad et al (1989) Pollen parent, reciprocal cross 10-70 days after pollination (DAP) NN (1969) and MS (1962) media; gibberellic acid (GA 3 ), indole-3-acetic acid (IAA), benzyladenine (BA), sucrose Gray et al (1990) Plant growth regulators (PGRs: chlormequat (CCC), uniconazole) Ledbetter and Shonnard (1990) 29 Genotypes Ramming (1990) Pollen parent Ramming et al (1990a) Reciprocal cross 52 and 66 DAA NN medium with IAA, GA 3 and active charcoal (AC) Tsolova (1990) Seedcoat manipulation Fernandez et al (1991) 10-40 DAA MS, White's (1954) and NN media;…”
Section: Genotypementioning
confidence: 99%
See 3 more Smart Citations
“…indole butyric acid (IBA), Ergostim, tartaric acid, L-glutamine and Lcysteine Emershad and Ramming (1984) Several genotypes Amino acids Emershad et al (1989) Pollen parent, reciprocal cross 10-70 days after pollination (DAP) NN (1969) and MS (1962) media; gibberellic acid (GA 3 ), indole-3-acetic acid (IAA), benzyladenine (BA), sucrose Gray et al (1990) Plant growth regulators (PGRs: chlormequat (CCC), uniconazole) Ledbetter and Shonnard (1990) 29 Genotypes Ramming (1990) Pollen parent Ramming et al (1990a) Reciprocal cross 52 and 66 DAA NN medium with IAA, GA 3 and active charcoal (AC) Tsolova (1990) Seedcoat manipulation Fernandez et al (1991) 10-40 DAA MS, White's (1954) and NN media;…”
Section: Genotypementioning
confidence: 99%
“…Specifically, more embryos were produced when a seeded cultivar or a seedless cultivar which has large abortive seeds was used as male parent, compared to the results obtained from two seedless cultivars which have very small abortive seeds (Cain et al 1983). It is well known however, that both female and male parent genotypes can have great impact on the capacity for embryo formation, embryo germination and plant development in the context of grape embryo rescue (Ebadi et al 2004;Garcia et al 2000;Gray et al 1990;Ji et al 2013b;Li et al 2013;Liu et al 2008;Qi and Ding 2002;Spiegel-Roy et al 1985. In one report it was found that, using identical conditions, the rates of embryo germination and seedling formation obtained from ovule culture were much higher when Flame Seedless was used as female parent than when Perlette or Sultanina were used as female parents (Spiegel-Roy et al 1985).…”
Section: Genotypementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, this result was approximately the same as in previous reports (Spiegel-Roy et al 1985;Gray et al1990). It appeared that adding GA 3 (~0.35 mg l -1 ) and IAA (~1.75 mg l -1 ) in medium would be propitious to not only break the dormancy of embryo, but also promote the embryo germination and growth (Spiegel-Roy et al 1985;Gray et al 1990;Yamashita et al 1998). Nevertheless, differences of genotypes in response to GA 3 and IAA should not be ignorable in embryo rescue culture.…”
mentioning
confidence: 99%